Cover Feature: High‐Voltage Performance of Ni‐Rich NCA Cathodes: Linking Operating Voltage with Cathode Degradation (ChemElectroChem 22/2019). Issue 22 (24th October 2019) - David, Lamuel; Mohanty, Debasish; Geng, Linxiao; Ruther, Rose E.; Sefat, Athena S.; Cakmak, Ercan; Veith, Gabriel M.; Meyer, Harry M.; Wang, Hsin; Wood, David L.
Abstract : The Cover Feature illustrates extended‐battery electric vehicle (EV) driving range achieved through deep understanding of degradation mechanisms of lithium‐ion cathodes charged to high voltage. More information can be found in the Article by L. David et al. on page 5571 in Issue 22, 2019 (DOI: 10.1002/celc.201901338 ).